2019
DOI: 10.1136/bmjopen-2019-031560
|View full text |Cite
|
Sign up to set email alerts
|

Usability of existing alcohol survey data in South Africa: a qualitative analysis

Abstract: ObjectiveThis paper assesses the usability of existing alcohol survey data in South Africa (SA) by documenting the type of data available, identifying what possible analyses could be done using these existing datasets in SA and exploring limitations of the datasets.SettingsA desktop review and in-depth semistructured interviews were used to identify existing alcohol surveys in SA and assess their usability.ParticipantsWe interviewed 10 key researchers in alcohol policies and health economics in SA (four women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…Further, information on drinking patterns prior to these alcohol bans (that could serve as a baseline for assessing the impact of alcohol policy changes) is not readily available. In this setting, alcohol consumption data are not routinely collected from individuals seeking health care or the general population and when collected rarely includes detailed information on volume of alcohol consumed [17].…”
Section: Introductionmentioning
confidence: 99%
“…Further, information on drinking patterns prior to these alcohol bans (that could serve as a baseline for assessing the impact of alcohol policy changes) is not readily available. In this setting, alcohol consumption data are not routinely collected from individuals seeking health care or the general population and when collected rarely includes detailed information on volume of alcohol consumed [17].…”
Section: Introductionmentioning
confidence: 99%
“…Another study in South Africa has found that although alcohol consumption is a major problem, the challenge is that most researches on alcohol consumption and its impact in South Africa have had difficulty in characterising the extent and distribution at the societal level of alcohol-related harm because of data constraints (Fontes Marx, London, Harker Burnhams, & Ataguba, 2019). Compatibly, the extent to which companies in South Africa utilise workplace testing appear to be unrecorded apart from the vast information on suppliers of breathalyser instruments, which suggest a market demand for workplace testing.…”
Section: Literaturementioning
confidence: 99%
“…Nonetheless, alcohol outlet density is proven to correlate with alcohol consumption, and this information provides insights and value as the study area population is at high risk for FAS and other alcohol-related harms. Fontes and colleagues have pointed to the need for accurate consumption data at household and community levels as important for informing public policy for alcohol harm-reduction, including FAS prevention [33].…”
Section: Alcohol Outlet Densitymentioning
confidence: 99%